Status Anemia dan Skor Diet Quality Index (DQI) pada Remaja Putri di SMP Ibnu Aqil, Bogor - Elma Alfiah; Andi Mukramin Yusuf; Amalina Ratih Puspa (Universitas Al Azhar Indonesia, 2021)
Anemia is a global health problem, which occurs in both developed and developing countries. The Indonesian Basic Health Research showed that the prevalence of anemia in adolescent girls aged 15-24 years was 48.9% in 2018. This study aimed to analyze the anemia status and diet quality index (DQI) of adolescent girls. The study was a cross-sectional conducted at Ibnu Aqil Junior High School, Ciomas District, Bogor from March to September 2019. The number of students involved as respondents in this study was 84 students. The results show that the prevalence of anemia in adolescent girls was 16.7%, with the mean Diet Quality Index (DQI) score indicating a low diet quality category (55.9 out of 100). There was no significant relationship between hemoglobin levels and DQI scores, but several indicators such as variations in protein source groups, fiber adequacy, iron adequacy, calcium adequacy, total fat moderation, and saturated fat moderation on adolescent girls who suffered anemia showed lower values than with those who didn’t suffer from anemia. The high prevalence of anemia could be caused by poor diet quality aspects, thus diet-based intervention should be the strategic solution to solve this problem. The high prevalence of anemia could be caused by poor diet quality aspects, thus diet-based intervention should be the strategic solution to solve this problem.Keyword - Adolescence, Anemia, Diet quality, DQI, Supplementation